Prediction of failure load of RC and R-ECC dapped-end beams - Mohammed, B.S. (Elsevier Ltd, 2020)
The dapped-end reinforcements of a control beam have been designed conforming to requirement of the PCI code. The dapped-end reinforcements of other beams were derived from the control beam that involve the scheme variation of the hanger or diagonal reinforcements. Some selected beams utilize the engineered cementitious composites (ECC) in the dapped-end region. Twenty-seven large-scaled beams with dapped-end have been prepared, cast and tested. All beams were tested under the three-point loading up to failure. To localize effect of the shear failure, the shear span-depth ratio (av/d) of 1.43 has been carried out. Dapped-end beam (DEB) specified in PCI code has nominal shear span-depth ratio (an/d) less than 1, but in this study, several beams use an/d larger than 1. For analytical purpose, the design equations specified in PCI code have been used for the analysis requirement. By comparing against the test results, the analysis results that using the design equations of PCI code provide a significant difference, in which the mean value of analysis-test results ratio is 0.71. The design equations specified in PCI code were reliable to design the dapped-end reinforcements, but these equations have not yet able to accommodate adequately, in analyzing and predicting the failure load of DEBs that have the dapped-end reinforcements scheme varied. Â© 2020 The Author(s)